Strengthening Uganda’s solar pump subsidy program: Key challenges and solutions - Kato, Edward; Ringler, Claudia; Kiguli, Geoffrey; Sentumbwe, George; Tiishekwa, Dennis; Nsereko, Abdul; Alinaitwe, Jennifer (International Food Policy Research Institute, 2024)
Despite rapidly increasing impacts of climate change, the adoption of irrigation technologies in Uganda remains limited, with no more than 2% of Ugandan farms irrigating any of their plots. To accelerate commercialization of agriculture and enhance the climate resilience of the country’s agri-food systems, the government of Uganda—through the Ministry of Agriculture, Animal Industry, and Fisheries, and with assistance from the World Bank—is implementing a subsidy program to help Ugandan farmers acquire solar pumps for small-scale irrigation.